A Note on Generalized Strongly p-Convex Functions of Higher Order - Corina Karim; Ekadion Maulana (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2022)
Generalized strongly -convex functions of higher order is a new concept of convex functions which introduced by Saleem et al. in 2020. The Schur type inequality for generalized strongly -convex functions of higher order also studied by them. This paper aims to revise Schur type inequality for generalized strongly -convex functions of higher order in their paper. In order to revise it, we show that the contradiction was true. This paper showed that  Schur type inequality for generalized strongly -convex functions of higher order previously is not valid and we give the correct Schur type inequality for generalized strongly -convex functions of higher order